EFFECT OF SERENE BUSINESS ENVIRONMENT ON THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN MALAYSIA (Malaysian Management Journal, 2023)
The effect of business environment on the performance of small and medium enterprises (SMEs) has been widely studied. Nevertheless, research on the effect of a serene business environment on the performance of SMEs is insufficient, notably in the context of Malaysia. Therefore, this study examined the effect of a serene business environment on SMEs’ performance in Malaysia. Related literature was critically reviewed, and five hypotheses on the effect of serene business environmental factors on performance were formulated. By adopting the cross-sectional survey design, the data of 148 respondents were collected and analyzed using descriptive and inferential statistical tools – Statistical Package for Social Sciences (SPSS) and Partial Least Square – Structural Equation Modeling (PLS-SEM). From the empirical findings, Malaysia’s serene business environment is critical in stimulating the performance of SMEs. Financial market environment, technological environment, and regulatory environment exerted a positive significant effect on SMEs’ performance. Nonetheless, economic environment and competitive environment indicated a strong, but negative significant effect on SMEs’ performance. These findings proposed new insights in this field of research by providing relevant research implications and suitable recommendations to business managers and policymakers in Malaysia.